2023
DOI: 10.1097/apo.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Durability, and Safety of Faricimab in Patients From Asian Countries With Diabetic Macular Edema: 1-Year Subgroup Analysis of the Phase III YOSEMITE and RHINE Trials

Susumu Ishida,
Shih-Jen Chen,
Toshinori Murata
et al.

Abstract: Purpose: To assess the 1-year efficacy, durability, and safety of faricimab in patients with diabetic macular edema from Asian and non-Asian countries. Design: Global, multicenter, randomized, double-masked, active comparator-controlled, phase III trials. Methods: Subgroup analysis of patients from Asian (N=144) and non-Asian (N=1747) countries randomized to faricimab 6.0 mg every 8 weeks (Q8W), faricimab pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These results are consistent with those of the YOSEMITE and RHINE studies, which reported that the efficacy of faricimab was not inferior to that of aflibercept 2 . In addition, a subgroup analysis of patients in the YOSEMITE and RHINE trials revealed similar results in Asian and non-Asian countries 8 and when limited to the patients in Japan 9 . Kusuhara et al reported that the overall mean CMT after switching from IVA to IVF decreased significantly from the baseline value 1 month after administration 10 .…”
Section: Discussionmentioning
confidence: 70%
“…These results are consistent with those of the YOSEMITE and RHINE studies, which reported that the efficacy of faricimab was not inferior to that of aflibercept 2 . In addition, a subgroup analysis of patients in the YOSEMITE and RHINE trials revealed similar results in Asian and non-Asian countries 8 and when limited to the patients in Japan 9 . Kusuhara et al reported that the overall mean CMT after switching from IVA to IVF decreased significantly from the baseline value 1 month after administration 10 .…”
Section: Discussionmentioning
confidence: 70%
“…A systematic literature review identified 26 randomized clinical trials published before August 2021 that were used to conduct a network meta-analysis to compare faricimab treatment and extend to intravitreal aflibercept, ranibizumab, bevacizumab, dexamethasone implant and laser treatment [181]. Network meta-analysis allow treatments that are not compared directly within randomized clinical trials to be compared indirectly.…”
Section: Combination Therapy Of Anti-ang2 and Anti-vegfmentioning
confidence: 99%
“…In this network meta-analysis at 12 months of follow-up, treatment and extended treatment regimen for faricimab demonstrated superior retinal drying which was achieved with fewer injections when compared to other flexible dosing regimens. In addition, visual outcomes at 12 months were superior with the treat and extend faricimab when compared to bevacizumab and ranibizumab [181]. Another systematic review and meta-analysis of three randomized clinical trials from 2013 to 2023 that included 2120 patients with DME concluded that faricimab was a better drying agent as manifested by a greater reduction in CST compared to other anti-VEGF agents [182].…”
Section: Combination Therapy Of Anti-ang2 and Anti-vegfmentioning
confidence: 99%